Accessing medicines for non-communicable diseases: Patients and health care workers’ experiences at public and private health facilities in Uganda - Tusubira, Andrew K.; Akiteng, Ann R.; Nakirya, Brenda D.; Nalwoga, Ritah; Ssinabulya, Isaac; Nalwadda, Christine K.; Schwartz, Jeremy I. (PloS one, 2020)
Non-communicable diseases (NCDs) are increasingly prevalent in low- and middle-income countries. Successful management requires consistent access to appropriate medicines. Availability of NCD medicines is generally low, especially in the public sector, however, little is known about other factors affecting access. We explored barriers and facilitators of access to medicines for diabetes and hypertension at public and private health facilities in Uganda. We conducted a qualitative descriptive study at six public hospitals and five private health facilities in different regions of Uganda. Data collection included 36 in-depth interviews and 14 focus group discussions (n = 128) among purposively selected adult outpatients with diabetes and/or hypertension and 26 key informant interviews with healthcare workers and patient association leaders. Transcripts were coded and emerging themes identified using the Framework method. Four main themes emerged: Stocking of medicines and supplies, Financial factors, Individual behaviour and attitudes, and Service delivery at health facilities. Stocking of medicines and supplies mainly presented barriers to access at public facilities including frequent stockouts, failure to stock certain medicines and low quality brands often rejected by patients. Financial factors, especially high cost of medicines and limited insurance coverage, were barriers in private facilities. Free service provision was a facilitator at public facilities. Patients' confusion resulting from mixed messages and their preference for herbal treatments were cross-sector barriers. While flexibility in NCD service provision was a facilitator at private facilities, provider burnout and limited operating hours were barriers in public facilities. Patient-driven associations exist at some public facilities and help mitigate inadequate medicine stock. Access to NCD medicines in Uganda is influenced by both health system and patient factors. Some factors are sector-specific, while others cross-cutting between public and private sectors. Due to commonalities in barriers, potential strategies for overcoming them may include patient-driven associations, public-private partnerships, and multi-modal health education platforms.